Partial Discharge characterization based on leakage current pulses waveform for contaminated glass insulator string - Othman, Nordiana Azlin (2015)
Partial discharge (PD) is an electrical discharge event that does not completely bridges the electrodes in the insulation systems under applied field. Although PD does not cause immediate breakdown of the insulation, it may affect the insulation performance in the long term due to repetition of PD events. The occurrence of PD causes leakage current (LC) to flow, thus an attempt to characterize PD based on LC pulses waveform is presented in this paper. Results show that PD can be characterized (according to their occurrence with respect to the AC supply) as follows: corona discharge occurring in lightly contaminated insulators, surface discharge occurring in medium contaminated insulators and finally internal discharge occurring in heavily contaminated insulators. The ability to distinguish the type of PDs from the LC waveform could be used to monitor and predict the condition of the insulator. The outcome can be incorporated in a conditioning monitoring system.